2021
DOI: 10.1093/noajnl/vdab092
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative imaging of glioblastoma patients using hyperpolarized 13C pyruvate: Potential role in clinical decision making

Abstract: Background Glioblastoma remains incurable despite treatment with surgery, radiation therapy, and cytotoxic chemotherapy, prompting the search for a metabolic pathway unique to glioblastoma cells. 13C MR spectroscopic imaging with hyperpolarized pyruvate can demonstrate alterations in pyruvate metabolism in these tumors. Methods Three patients with diagnostic MRI suggestive of a glioblastoma were scanned at 3T 1-2 days prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 30 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…Previous clinical studies using 13 C MRI with hyperpolarized [1- 13 C]pyruvate have demonstrated the feasibility of imaging GBM metabolism in patients across a spectrum of clinical presentations, all performed following some form of treatment ( 19 23 ). Moreover, a correlation between gene expression and lactate labeling has not been demonstrated previously ( 19 25 ). In this exploratory study, we have characterized hyperpolarized [1- 13 C]pyruvate metabolism in participants with treatment-naive isocitrate dehydrogenase wild-type GBM by using hyperpolarized 13 C MRI.…”
Section: Introductionmentioning
confidence: 76%
“…Previous clinical studies using 13 C MRI with hyperpolarized [1- 13 C]pyruvate have demonstrated the feasibility of imaging GBM metabolism in patients across a spectrum of clinical presentations, all performed following some form of treatment ( 19 23 ). Moreover, a correlation between gene expression and lactate labeling has not been demonstrated previously ( 19 25 ). In this exploratory study, we have characterized hyperpolarized [1- 13 C]pyruvate metabolism in participants with treatment-naive isocitrate dehydrogenase wild-type GBM by using hyperpolarized 13 C MRI.…”
Section: Introductionmentioning
confidence: 76%
“…As mentioned earlier, most studies focus on detecting and following prostate cancers , and the potential metastasis to bone and liver (Figure ). Other studies have also shown the great potential of d DNP for detecting breast cancer, or brain metabolism and glioblastoma . More recently, detection of renal tumors and even whole abdomen metabolism was reported.…”
Section: Hyperpolarization Techniquesmentioning
confidence: 98%
“…Other studies have also shown the great potential of dDNP for detecting breast cancer, 367 or brain metabolism 370 and glioblastoma. 371 More recently, detection of renal tumors 372 and even whole abdomen metabolism 373 was reported.…”
Section: Practical Aspectsmentioning
confidence: 99%
“…Recent advances in clinical translation of HP pyruvate imaging 15 has enabled metabolic imaging of the human brain in healthy subjects 16,17 and patients with brain tumors 17–20 or TBI 21 . Most previous human brain studies focused on imaging altered lactate production in intracranial malignancies 18,19 .…”
Section: Introductionmentioning
confidence: 99%